1996
DOI: 10.1021/jf950753i
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Supercritical CO2 on Myrosinase Activity and Glucosinolate Degradation in Canola

Abstract: The effect of supercritical carbon dioxide (SC-CO2) extraction conditions (temperature, pressure, extraction time, and moisture content of the samples) on the myrosinase activity and glucosinolate hydrolysis in flaked and whole canola seeds was studied. Combined effects of high temperature (75 °C), pressure (62.1 MPa), and moisture (∼20% w/w) were necessary to achieve 90% enzyme inactivation in canola flakes in 3 h. Similar extraction conditions resulted in only 44% enzyme inactivation in whole canola seeds. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 27 publications
1
17
0
1
Order By: Relevance
“…Similarly, as prolonging the treatment time from 5 to 60 min at 22 MPa and 55 °C, it decreased from 60.74 to 18.18%. However, Dunford & Temelli (1996) investigated the inactivation of MYR exposed to supercritical CO 2 in canola flakes with 19% moisture content at 21.4, 41.4 and 62.1 MPa and 55 °C, no significant reduction of MYR activity was found. It was assumed that lower moisture content increased the resistance of MYR to supercritical CO 2.…”
Section: Resultsmentioning
confidence: 97%
“…Similarly, as prolonging the treatment time from 5 to 60 min at 22 MPa and 55 °C, it decreased from 60.74 to 18.18%. However, Dunford & Temelli (1996) investigated the inactivation of MYR exposed to supercritical CO 2 in canola flakes with 19% moisture content at 21.4, 41.4 and 62.1 MPa and 55 °C, no significant reduction of MYR activity was found. It was assumed that lower moisture content increased the resistance of MYR to supercritical CO 2.…”
Section: Resultsmentioning
confidence: 97%
“…70, which is in the recommended range for oilseed extraction [31]. The oilseeds were then oven-dried at 104°C for 35 min to inactivate myrosinase enzymes, gossypols and other unfavorable compounds [31,32]. Moisture level in the oilseeds were determined by AOAC standard procedure (Method 925.40) [33].…”
Section: Oilseed Pretreatmentmentioning
confidence: 99%
“…Chulalaksananukul et al [7] showed that the stability of immobilized lipase from Mucor mihei is always decreased after addition of water at temperature between 40 and 100°C. The combined eVects of high pressure, temperature and moisture content are even used to achieve inactivation of enzymes resulting in a lower seed quality [9]. The extent to which water content inXuences on stability of lipase depends on the hydrophobicity of the media, the immobilized supporter and the type of enzyme.…”
Section: Water Content Inxuence On Stability Of Lipasementioning
confidence: 99%